Block of motor nerve conduction via transcutaneous application of direct current. Issue 2 (25th May 2018) - Van Acker, Gustaf M; Vrabec, Tina L; Bhadra, Narendra; Chae, John; Kilgore, Kevin L; Bhadra, Niloy
Aims: Nerve conduction block using implanted electrodes is being used increasingly for clinical applications. Alternatively, non-invasive electrical nerve block would be beneficial for applications including pain block and muscle spasticity. Here we developed a novel means of non-invasive electrical nerve conduction blockade – transcutaneous direct current block (tDCB) – that produces direct block of nerve conduction.Materials & Methods: In an in vivo rodent model, tDCB produced stable neuromotor blockade of sciatic nerve branches, dependent on stimulus parameters and electrode geometry.Results: Partial-to-complete neuromotor block was achieved in all subjects using tDCB amplitudes at or below 20 mA, and complete block was achieved at amplitudes as low as 6 mA.Conclusions: Our results reveal that neuromotor activity can be rapidly, reliably and reversibly blocked using tDCB.